Autophagy Modulators From Chinese Herbal Medicines: Mechanisms and Therapeutic Potentials for Asthma - Zhang, Yun; Wang, Xing; Zhang, He; Tang, Hongmei; Hu, Hang; Wang, Songping; Wong, Vincent Kam Wai; Li, Yuying; Deng, Jun (Frontiers in Pharmacology, 2021)
Asthma has become a global health issue, suffering more than 300 million people in the world, which is a heterogeneous disease, usually characterized by chronic airway inflammation and airway hyperreactivity. Combination of inhaled corticosteroids (ICS) and long acting β-agonists (LABA) can relieve asthma symptoms and reduce the frequency of exacerbations, especially for patients with refractory asthma, but there are limited treatment options for people who do not gain control on combination ICS/LABA. The increase in ICS dose generally provides little additional benefit, and there is an increased risk of side effects. Therefore, therapeutic interventions integrating the use of different agents that focus on different targets are needed to overcome this set of diseases. Some findings suggest autophagy is closely correlated with the severity of asthma through eosinophilic inflammation, and its modulation may provide novel therapeutic approaches for severe allergic asthma. The chinese herbal medicine (CHM) have been demonstrated clinically as potent therapeutic interventions for asthma. Moreover some reports have found that the bioactive components isolated from CHM could modulate autophagy, and exhibit potent Anti-inflammatory activity. These findings have implied the potential for CHMs in asthma or allergic inflammation therapy via the modulation of autophagy. In this review, we discuss the basic pathomechanisms underpinning asthma, and the potential role of CHMs in treating asthma with modulating autophagy.